The Potential of Kaliandra Honey (Calliandra sp.) on Sertoli Cell Counts in Malnourished Albino Rats - Erlangga, Made Bagus; Srianto, Pudji; Safitri, Erma; Rimayanti, Rimayanti; Hernawati, Tatik; Hermadi, Herry Agoes (Jurnal Medik Veteriner, 2023)
This study was performed to investigate the effect of calliandra honey (Calliandra sp.) on the number of sertoli cells in malnourished male albino rats. A total of 24 male rats were divided into four groups, i.e. (K) without treatment, (P0) fasted, (P1 and P2) respectively fasted and administered honey concentrations of 30% and 50% for 10 days after fasting. The results showed that administration calliandra honey with a concentration of 30% and 50% significantly increased the number of sertoli cells. It can be concluded that administration calliandra honey can have a positive effect on malnourished male rats, especially in improving the number of sertoli cells.